2018
DOI: 10.1371/journal.pntd.0006160
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel leishmanicidal molecules by virtual and biochemical screenings targeting Leishmania eukaryotic translation initiation factor 4A

Abstract: Leishmaniases are neglected parasitic diseases in spite of the major burden they inflict on public health. The identification of novel drugs and targets constitutes a research priority. For that purpose we used Leishmania infantum initiation factor 4A (LieIF), an essential translation initiation factor that belongs to the DEAD-box proteins family, as a potential drug target. We modeled its structure and identified two potential binding sites. A virtual screening of a diverse chemical library was performed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 105 publications
0
28
1
Order By: Relevance
“…The remaining cells were lysed by SDS (0.01 %), and the pellets were washed with PBS and resuspended in 100 μL Schneider medium supplemented with 10 % FBS and cultured at 22 °C in 96 well-plates. Parasites viability was assessed right after the lysis of the cells and 24 h later, by a Methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay as described previously (Harigua-Souiai et al, 2018). Briefly, 20 μL of MTT (5 mg/mL) were added to each well and incubated at 22 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining cells were lysed by SDS (0.01 %), and the pellets were washed with PBS and resuspended in 100 μL Schneider medium supplemented with 10 % FBS and cultured at 22 °C in 96 well-plates. Parasites viability was assessed right after the lysis of the cells and 24 h later, by a Methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay as described previously (Harigua-Souiai et al, 2018). Briefly, 20 μL of MTT (5 mg/mL) were added to each well and incubated at 22 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Scientific, Waltham, MA, USA). The RNA products were separated by electrophoresis on a 15 8% PAGE gel containing 7 M urea, and the band corresponding to the desired product was 16 eluted, extracted with phenol, extracted with chloroform-isoamyl alcohol (24:1) and ethanol 17 precipitated as previously described [28]. The centrifuged and dried pellet was resuspended in 18 20 mM Tris-HCl, pH 7.5, 0.1 mM EDTA and stored at -20 °C until needed.…”
Section: Rna Helicase Activity 10mentioning
confidence: 99%
“…Moreover, the majority of the Leishmania and Trypanosoma genes are constitutively expressed as polycistronic RNAs that are subsequently processed into separate capped and polyadenylated mRNAs; thus, translation, and probably DDX3-like proteins, plays a particularly important role in the control of gene expression, especially for the differentiation into the different parasitic forms (reviewed by [ 49 , 50 , 51 ]). Indeed, we previously showed that the eIF4A-like translation protein, LieIF4A (LINF_010012800/LINF_010012900), is a viable target for therapeutic drugs [ 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%